2015
DOI: 10.1017/s0142716415000600
|View full text |Cite
|
Sign up to set email alerts
|

Performance pressure enhances speech learning

Abstract: Real-world speech learning often occurs in high pressure situations such as trying to communicate in a foreign country. However, the impact of pressure on speech learning success is largely unexplored. In this study, adult, native speakers of English learned non-native speech categories under pressure or no-pressure conditions. In the pressure conditions, participants were informed that they were paired with a (fictitious) partner, and that each had to independently exceed a performance criterion for both to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 111 publications
1
9
0
Order By: Relevance
“…Such a type of performance pressure improved the learning of multi-dimensional categories whose learning is based on the procedural learning system, but impaired the learning of rulebased categories whose learning is assumed to depend on the declarative learning system. A similar finding was also observed in procedural learning of speech categories (Maddox et al, 2016). Stress was also found to influence procedural reinforcement learning (Petzold et al, 2010).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Such a type of performance pressure improved the learning of multi-dimensional categories whose learning is based on the procedural learning system, but impaired the learning of rulebased categories whose learning is assumed to depend on the declarative learning system. A similar finding was also observed in procedural learning of speech categories (Maddox et al, 2016). Stress was also found to influence procedural reinforcement learning (Petzold et al, 2010).…”
Section: Introductionsupporting
confidence: 81%
“…Furthermore, the neuroimaging data in the same study revealed hippocampal activity during task performance devoid of the stress manipulation, whereas striatal activation was observed when performing the task under stressful conditions. Stressinduced effects on further procedural striatal-based learning tasks were documented in visual category learning (Markman et al, 2006;Ell et al, 2011;McCoy et al, 2014), speech category learning (Maddox et al, 2016), and reinforcement learning (Cavanagh et al, 2010;Petzold et al, 2010). In the study conducted by Markman et al (2006), participants were convinced that their performance would determine whether they and a fabricated companion would earn a monetary bonus.…”
Section: Introductionmentioning
confidence: 99%
“…The two stimulation groups differed only on whether tVNS was paired with the tone categories that were easier-to-learn (Tone 1 and Tone 3; "tVNS-easy group") or harder-to-learn (Tone 2 and Tone 4; "tVNS-hard group"). These tone categories were selected on an empirical basis, based on a cohort of 678 English learners of Mandarin tones (Aggregate dataset) collected across eight published studies using no stimulation 9,13,15,16,36,37,40 (see "Aggregate dataset" in the Methods; Fig. 1b left).…”
Section: Resultsmentioning
confidence: 99%
“…Prior speech category training work has demonstrated that changes in arousal induced by performance pressure or selective attention to task-relevant acoustic cues enhances learning 36,37 . Given the expected modulatory effects of electrical stimulation on auditory sensory plasticity and arousal, we predicted that tVNS would enhance speech category learning selectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the “Results” section, we include Number of Linear Blocks as a dependent measure in multiple-linear-regression models (alongside accuracy in the 6th training block). Below, we provide specific details on the modeling procedures (additional details are available in several previous papers, e.g., Maddox and Ashby, 1993 ; Maddox, 1999 ; Maddox et al, 2016 ; Noh et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%